Manajemen Sekolah sebagai Wadah dalam Peningkatan Pendidikan Bermutu - Setiawan, Farid; Gio, Muhammad; Iza, Salsa Nurul; T, Hesty Andriani (Lembaga Yasin AlSys, 2022)
The problem that often occurs in the world of education is the lack of proper education. One of the reasons for this is the lack of proper school management. Education really needs aspects that can improve the quality and quality in empowering the community, starting with students. Students who will become the nation's next generation certainly need good quality education. As a vehicle as well as a means and in studying institutions, of course education or institutions must be of high quality. School residents, the community and the government certainly have an important role in the progress of education. Cooperation between various aspects is certainly very influential on the goal of improving the quality of education. From the above problems, this explains the need for efforts to improve education management. This article uses literature research, by looking for sources of reference material from journals and books that discuss themes related to studies that discuss the nature of educator management and its functions and uses. After the data supporting materials and reference materials are collected, the next step is compiling by analyzing according to the reality that occurs with intellect.